2022
DOI: 10.20517/2347-9264.2021.128
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic lymphedema: review of the literature and surgical treatment options

Abstract: Post-traumatic lymphedema (PTL) is a complex, debilitating, and potentially common disease which has received limited attention to date. The available literature is reviewed to identify injury patterns and critical lymphatic areas associated with the disease. A deeper understanding of these critical anatomic regions allows the reconstructive surgeon to potentially identify PTL patients earlier in order to apply surgical and nonsurgical interventions in the acute phase, improving lymphatic physiology and, ultim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…19,20 Posttraumatic extremity lymphedema incidence is unknown and the problem is underdiagnosed. 26 It is demonstrated that after limb trauma, even without physical disruption of the superficial lymphatic system, 100% of the patients can experience edema due to increased lymphatic production from local inflammation, which is thought to be a contributing mechanism. There is a group of patients in which the edema resolves spontaneously, probably due to a remitted inflammatory process rather than resolved lymphatic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Posttraumatic extremity lymphedema incidence is unknown and the problem is underdiagnosed. 26 It is demonstrated that after limb trauma, even without physical disruption of the superficial lymphatic system, 100% of the patients can experience edema due to increased lymphatic production from local inflammation, which is thought to be a contributing mechanism. There is a group of patients in which the edema resolves spontaneously, probably due to a remitted inflammatory process rather than resolved lymphatic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Another common cause of secondary lymphedema in humans is post-traumatic lymphedema [ 28 ]. The majority of reported cases describe a fracture as initiating event, but also burns, penetrating, and blunt injuries, resulting in the disruption of the cisterna chyli, thoracic duct, or other regions of increased density of lymphatic vessels, e.g., extremities are reported.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, there was neither prior history of trauma, nor clinical findings, suggesting a previous injury. These data, together with the results of indirect CT lymphography of the patient and the fact that minor trauma rarely leads to chronic lymphedema, make this mechanism of development of lymphedema in this dog highly unlikely [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, most peripheral superficial lymphatic vessels of the lower leg run along the way of the medial face of the limb, parallel to the superficial great saphenous vein [21] damage, chronic inflammation, and trauma to this specific anatomic area contribute to the development of secondary lower limb lymphedema [22][23][24][25][26]. This site was exactly the spider bite site, where local loxoscelism was developed, where the skin and soft tissue destruction happened to be; the epicenter of the chronic inflammatory process caused by the wound, and where recurrent lymphangitis originated.…”
Section: Fig 3 Wound Detail Note the Broad Rings Of Fibrous And Devit...mentioning
confidence: 99%